2013
DOI: 10.1007/s00397-013-0706-6
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic melt rheology and time–temperature superposition of polycarbonate–multi-walled carbon nanotube nanocomposites

Abstract: This work investigates the linear and non-linear viscoelastic melt rheology of four grades of polycarbonate melt compounded with 3 wt% Nanocyl NC7000 multiwalled carbon nanotubes and of the matching matrix polymers. Amplitude sweeps reveal an earlier onset of nonlinearity and a strain overshoot in the nanocomposites. Mastercurves are constructed from isothermal frequency sweeps using vertical and horizontal shifting. Although all nanocomposites exhibit a second plateau at ∼10 5 Pa, the relaxation times estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…The slower cooling process in CM specimens provides an explanation, promoting a more percolated network and secondary agglomeration, and leading to a wider variation in the CNT network compared to IM specimens. This is consistent with the view that polymer mobility dominates the relaxation processes [3]. A smaller effect contributing to the higher resistivity of IM bars may be orientation of CNTs due to skin effects [9].…”
Section: Electrical Resistivitysupporting
confidence: 90%
See 1 more Smart Citation
“…The slower cooling process in CM specimens provides an explanation, promoting a more percolated network and secondary agglomeration, and leading to a wider variation in the CNT network compared to IM specimens. This is consistent with the view that polymer mobility dominates the relaxation processes [3]. A smaller effect contributing to the higher resistivity of IM bars may be orientation of CNTs due to skin effects [9].…”
Section: Electrical Resistivitysupporting
confidence: 90%
“…They confirmed that the CNT network consists of weakly bonded clusters that break up and re-agglomerate to form a conductive pathway during the application of shear, suggesting that the destruction of CNT-CNT bonds is reversible. Recent work carried out in our laboratory also confirmed the polymer's role as the dominant relaxation mechanism in these nanocomposite materials [3].…”
Section: Introductionsupporting
confidence: 56%
“…[1], and of PC from ref. [5]. Linear rheology of PLA was measured using a Bohlin C-VOR Instruments rheometer fitted with an environmental chamber.…”
Section: Methodsmentioning
confidence: 99%
“…One factor that affects the breadth of the distribution is the exponent of 3.4 in Equation (3). There are some suggestions that this exponent can be polymer specific -for instance, values of 4.2 [7] and 5.7 [5] have been reported for PC. A higher exponent narrows the width of the distribution, and therefore it is unlikely that this is the explanation for the discrepancy observed here.…”
Section: Determination Of the Scaling Constantmentioning
confidence: 99%
See 1 more Smart Citation